PWE-100 Challenges in adhering to a gluten free diet in different ethnic groups. (8th June 2018) - Muhammad, Humayun; Reeves, Sue; Ishaq, Sauid; Mayberry, John; Jeanes, Yvonne
Abstract : Introduction: The treatment for Coeliac Disease (CD) is a lifelong strict gluten free diet (GFD) to prevent comorbidities. Patients refer to both social and practical challenges with adhering to a GFD (Lerner, 2010). There is very limited research exploring the challenges of a GFD in ethnic populations residing in the UK. This study aimed to determine if the challenges in dietary adherence to a GFD were similar for South Asian (SA) and White Ethnicity (WE) populations with CD. Methods: A combined cross sectional survey using validated questionnaire and CD adherence score (Leffler) and review of clinical and laboratory data was utilised. A score of 13 or less was used to determine the non-adherence (Mooney et al. 2014). 972 (histologically confirmed CD) patients (85% White, 86% Female) were approached through postal route. Semi-structured mixed qualitative and quantitative method telephonic interviews were conducted in 28 patients with CD not adhering to a GFD (SA=7, WE=21). Results: SA (13; 10–19, n=38) and WE patients (13; 10–19, n=375) with CD (13; 10–19, n=375); 52.2% and 52.6% respectively were categorised as adhering to a GFD. Interviews with patients not adhering to a GFD highlighted 54% of WE indicated motivation as a challenge compared with 33% of SA, whereas, 77% of SA indicated contamination as an issue compared with 4% of WE patients. Both SA and WE patients found eating out difficult (80% and 86% respectively), with the majority of each group indicating a lack of confidence in the knowledge of restaurant staff (85% and 66% respectively). 85% of SA patients with CD reported not finding GF foods in their local Asian stores Conclusions: Our study highlights that there are substantial issues with the understanding of food labels that impact adherence to a GFD. Furthermore, the absence of GF foods in local Asian stores is likely to reduce adherence. More research is required to quantify the low availability of GF foods in local Asian stores. References: . Lerner, A. New therapeutic strategies for celiac disease. Autoimmunity Reviews2010;9(3):144–147. . Mooney, P. D., Leeds, J. S., Libzo, et al., (2014) Case-finding for coeliac disease in secondary care: Digestive and Liver Disease: Official Journal of the Italian Society of Gastroenterology and the Italian Association for the Study of the Liver. 46(1):32–35.